Podoplanin is required for tumor cell invasion in cutaneous squamous cell carcinoma. Issue 11 (9th April 2021) - Schwab, Melanie; Lohr, Sabrina; Schneider, Jakob; Kaiser, Michaela; Krunic, Damir; Helbig, Doris; Géraud, Cyrill; Angel, Peter
Abstract: The invasiveness of late‐stage cutaneous squamous cell carcinoma (cSCC) is associated with poor patients' prognosis and linked to strong upregulation of the glycoprotein Podoplanin (PDPN) in cancer cells. However, the function of PDPN in these processes in cSCC carcinogenesis has not been characterized in detail yet. Employing a CRISPR/Cas9‐based loss‐of‐function approach on murine cSCC cells, we show that the loss of Pdpn results in decreased migration and invasion in vitro. Complementing these in vitro studies, labelled murine control and Pdpn knockout cells were injected orthotopically into the dermis of nude mice to recapitulate the formation of human cSCC displaying a well‐differentiated morphology with a PDPN‐positive reaction in fibroblasts in the tumor stroma. Smaller tumors were observed upon Pdpn loss, which is associated with reduced tumor cell infiltration into the stroma. Utilizing Pdpn mutants in functional experiments in vitro, we provide evidence that both the intra‐ and extracellular domains are essential for cancer cell invasion. These findings underline the critical role of PDPN in cSCC progression and highlight potential therapeutic strategies targeting PDPN‐dependent cancer cell invasion, especially in late‐stage cSCC patients.